Economic evaluation of environmental dust phenomenon damage (case of study: Ardakan city) - Hadis Ghanavati; Ahmad Fatahi Ardakani; Akram Neshat (علوم محیطی)
Introduction: One of the air pollution that has been witnessed in western and southwestern regions of recent times is the dust and dust phenomenon. Dust is one of the atmospheric phenomena that has adverse environmental effects and impacts. Dust storms have had many negative effects on health, economics, society and the environment, resulting in huge damage to human resources, health, industry, and especially agriculture. The purpose of this study is to quantify the tangible (market) and intangible (non-market) damages caused by the dust phenomenon in the city of Ardakan. Materials and methods: The data required in this study were obtained from the statistics and data recorded in Ardakan offices, as well as the completion of 244 double bounded dichotomous choice questionnaires in agricultural sector and 509 questionnaires in the air pollution and urban green area using 30 pre-tests and Michels And Carson in 2016. In this study, the tangible and intangible damages of dust are valued using the conditional valuation method and market price. Using the logit model, the factors that affect the willingness to pay are estimated for each section using Shazam 9 and math calculations using Maple Version 18 software. Results and discussion: The results of this study showed that income and education variables have a positive and significant effect on people's willingness to pay for air pollution and urban green space. The variables of age, number of households and gender have a negative and significant effect on people's willingness to pay for air pollution and urban green space against dust phenomena. In agricultural sector, variables such as age, number of employed people, education and income have a positive and significant effect on farmers' willingness to pay for agricultural products against dust phenomena. The total value of the damages against the dust phenomena to maintain air pollution is 33185478480 Rials, the maintenance of agricultural products 50431570000 Rials and the maintenance of green space against dust of 30736160140 Rials per year for the city of Ardakan. Also the tangible losses of dust phenomena in terms of increasing water consumption due to washing in dusty days is 2762736640 Rials, negative effect of dust on physical health and treatment costs and mortality due to asthma and bronchitis diseases 15548414040 Rials and negative effect The livestock sector and treatment costs and the lost cattle were calculated 131451400000 Rials using a market approach. Conclusion: The results indicate that the total value of intangible damages is 114353208620 Rls and the tangible value of 149762550680 Rls in 2016 for the city of Ardakan. The value of willingness to pay people in agriculture was higher than other sectors. The livestock and poultry sector also has the highest figure among other tangible costs. Therefore, this estimate provides policy makers and authorities with the necessary guidance for controlling the effects of dust on human environments.